Gastroesophageal reflux disease and oral symptoms: A two-sample Mendelian randomization study - Jiang, Shijing; Zheng, Liang; Miao, Zhiwei (Frontiers in Genetics, 2023)
Background: The association between Gastroesophageal reflux disease (GERD) and oral symptoms has been reported in observational studies, but the causality of GERD to oral symptoms remained unknown. We aimed to assess the causal effect of GERD on five oral symptoms (mouth ulcers, toothache, loose teeth, bleeding gums, and periodontitis) using the two-sample Mendelian randomization (MR) method. Methods: Summary-level statistics for GERD and five oral symptoms were obtained from large-scale genome-wide association studies. Rigorous quality control of genetic instruments was conducted before MR analysis. Several analytical methods, including the inverse-variance weighted (IVW) method, MR-Egger regression, weighted median, maximum likelihood, and robust adjusted profile score (RAPS) were utilized, and the results of IVW were taken as the main results. The MR-Egger intercept test, Cochran’s Q test, and leave-one-out test were used as sensitivity analysis for quality control. Results: After Bonferroni, IVW detected a significant effect of GERD on mouth ulcers (OR = 1.008, 95% CI = 1.003-1.013, P = 0.003), loose teeth (OR = 1.009, 95% CI = 1.005-1.012, P = 9.20×10-7), and periodontitis (OR = 1.229, 95% CI = 1.081-1.398, P = 0.002). Consistent patterns of associations were observed across several MR models and sensitivity analysis found little evidence of bias. Nominal significant associations were observed in toothache and bleeding gums (P < 0.05), and heterogeneity was detected. Conclusions: Our MR analyses supported the positive causal effect of GERD on oral symptoms, especially for mouth ulcers, loose teeth, and periodontitis. Our findings might shed light on the mechanism of oral disease and might imply that oral care should be enhanced in patients with GERD.